REPRESENTASI PEREMPUAN DALAM MAJALAH WANITA - Liliek Budiastuti Wiratmo (Yinyang: Jurnal Studi Islam, Gender dan Anak, 2015)
The existence of women’s magazine expected as medium to give new spirit through article presentation that empower woman position on public domain. However, the reality is reversed. Those presentation and ideas contain tend to establish women’s magazine as lifestyle shaper and place woman as market for a variety of product